In situ precipitation: a novel approach for preparation of iron-oxide magnetoliposomes - Xia S (Dove Medical Press, 2014)
Shudong Xia,1 Peng Li,1 Qiang Chen,1 Malik Armah,2 Xiaoying Ying,3 Jian Wu,4 Jiangtao Lai51Yiwu Affiliated Hospital, College of Medicine, 2College of Medicine, 3College of Pharmacy, 4College of Nanotechnology, 5First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, People's Republic of ChinaBackground: Conventional methods of preparing magnetoliposomes are complicated and inefficient. A novel approach for magnetoliposomes preparation was investigated in the study reported here.Methods: FeCl3/FeCl2 solutions were hydrated with lipid films to obtain liposome-encapsulated iron ions by ultrasonic dispersion. Non-encapsulated iron ions were removed by dialysis. NH3 · H2O was added to the system to adjust the pH to a critical value. Four different systems were prepared. Each was incubated at a different temperature for a different length of time to facilitate the permeation of NH3 · H2O into the inner phase of the liposomes and the in situ formation of magnetic iron-oxide cores in the liposomes. Single-factor analysis and orthogonal-design experiments were applied to determinate the effects of alkalization pH, temperature, duration, and initial Fe concentration on encapsulation efficiency and drug loading.Results: The magnetoliposomes prepared by in situ precipitation had an average particle size of 168±14 nm, zeta potential of -26.2±1.9 mV and polydispersity index of 0.23±0.06. The iron-oxide cores were confirmed as Fe3O4 by X-ray diffraction and demonstrated a superparamagnetic response. Encapsulation efficiency ranged from 3% to 22%, while drug loading ranged from 0.2 to 1.58 mol Fe/mol lipid. The optimal conditions for in situ precipitation were found to be an alkalization pH of 12, temperature of 60°C, time of 60 minutes, and initial Fe concentration of 100 mM Fe3+ + 50 mM Fe2+.Conclusion: In situ precipitation could be a simple and efficient approach for the preparation of iron-oxide magnetoliposomes.Keywords: magnetoliposomes, in situ precipitation, iron oxide, alkalization, permeability